The interplay of personality traits and motivation in leisure travel decision-making during the pandemic - Sreen Naman; Tandon Anushree; Jabeen Fauzia; Srivastava Shalini; Dhir Amandeep (Elsevier, 2025)
COVID-19 has negatively affected the travel and tourism industry and may continue to do so in the future. Therefore, hospitality businesses need to pay attention to consumer reactions, concerns, and motives for trav-elling in this era. This study leverages the stimulus-organism-behaviour-consequence (SOBC) model to examine psychological factors that influence Japanese travellers' intention to travel and willingness to pay premiums for safe travel by analysing data from 790 respondents. The findings of the study reveal that extraversion positively associates with introjected motivation and negatively with amotivation. Neuroticism personality type positively associates with amotivation and negatively associates with introjected motivation. Introjected motivation positively associates with perception of safe travel during COVID-19, whereas amotivation has a non-significant association with perception of safe travel during COVID-19. Perception of safe travel positively associates with intention to travel and willingness to pay premiums for safe travel. Finally, intention to travel has no effect on willingness to pay premiums for safe travel. These findings provide valuable theoretical and managerial implications.